Exploring the effects of factors on the willingness of female employees to telecommute in Kuala Lumpur, Malaysia - Kadar Hamsa, Abdul Azeez; Mustafa, Mootaz Munjid; Ibrahim, Mansor; Mohamed, Mohd Zin; Zahari, Rustam Khairi (Elsevier, 2016)
Telecommuting is increasingly gaining attention in Malaysia as a means of both easing the worsening peak-hour traffic congestion, and retaining women in the workforce. Moreover, substantial evidence in the literature suggests that telecommuting is more suited to women who when compared to men, experience more work/non-work role conflict and more career interruptions. However, the incidence of actual telecommuting among female employees in Kuala Lumpur remains very limited. A survey of 454 women employed in the industries of financial intermediation, real estate, education and ICT in Kuala Lumpur, revealed that only 2% of the respondents were practicing telecommuters, and that more than a third (35%) of those who stated their ability to telecommute, were in fact unwilling to utilize that working arrangement if given the opportunity. The main aim of this study is to explore the factors contributing to the willingness to telecommute or the lack thereof. The significance of this study stems from the fact that a better understanding of what influences the willingness to telecommute is a prerequisite for the successful promotion of the practice, and thus reaping its well researched benefits. Job suitability, delay experienced in the morning commute, and the increased usage of Smartphone technology were found to have a positive correlation with the willingness to telework, whereas car ownership, household size, and the negative perceptions towards teleworking were found to have a negative correlation.